Reforming Fisheries and Aquaculture for Global Benefits : Evaluation Report - Williams, Meryl J. (World Bank, Washington, DC, 2014)
The World Bank had commissioned an independent team to evaluate and assess the future role of PROFISH, the Global Program on Fisheries. The evaluation team found that PROFISH, since its inception in 2005, had made excellent progress in raising World Bank, bilateral donor and client country awareness of fisheries development needs, contributed fisheries and aquaculture content to global development products and assisted World Bank country and regional operations. The evaluation team concluded that fisheries can be reformed to achieve multiple objectives by (1) focusing on governance and institutions, (2) including fisheries in the mainstream development agendas and in global themes such as food security and climate change, and (3) applying the key operational tools of problem diagnosis, sequenced interventions and implementation experience and learning.